2015
DOI: 10.1158/0008-5472.can-14-3216
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Fluid–Mosaic Structure and Cancer Metastasis

Abstract: Cancer cells are surrounded by a fluid-mosaic membrane that provides a highly dynamic structural barrier with the microenvironment, communication filter and transport, receptor and enzyme platform. This structure forms because of the physical properties of its constituents, which can move laterally and selectively within the membrane plane and associate with similar or different constituents, forming specific, functional domains. Over the years, data have accumulated on the amounts, structures, and mobilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 95 publications
0
76
0
1
Order By: Relevance
“…A bilayer can be seen as a continuous two-dimensional film consisting of two lipid monolayers of about 2–3nm thickness. Lipid molecules within the monolayers can be organized in persistent or dynamic domains of diverse lipid compositions and even different physical states (see for recent review [6]).…”
Section: Membrane Tensionmentioning
confidence: 99%
“…A bilayer can be seen as a continuous two-dimensional film consisting of two lipid monolayers of about 2–3nm thickness. Lipid molecules within the monolayers can be organized in persistent or dynamic domains of diverse lipid compositions and even different physical states (see for recent review [6]).…”
Section: Membrane Tensionmentioning
confidence: 99%
“…Recent studies have reported the specialized subcellular structures, which were named as invadopodia in malignant cells and podosomes in many normal cell types, including vascular endothelial cells, macrophages, osteoclasts, etc ., involved in the degradation of ECM [12, 13]. These membrane protrusions facilitate cancer cells penetration through the basement membrane of blood vessels and into surrounding tissues, therefore promoting local invasion and distant metastasis of the cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lipid rafts are typical of many human tumor cells, 23,24 thus representing a potential advantage for the therapeutic/diagnostic utilization of lipid nanovectors.…”
Section: Ultrastructural Morphology For Nanotechnologymentioning
confidence: 99%